ANALISIS PENGARUH KESADARAN WAJIB PAJAK, PENGHASILAN, KUALITAS PELAYANAN DAN SOSIALISASI TERHADAP KEPATUHAN MEMBAYAR PBB-P2 - Amelia Sandra; We Yayang Angelika (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
The realization of tax revenues from 2017-2019 does not meet the basic provisions set by the Pontianak city government. Taxpayer compliance can be due to the internal and external factors of the taxpayer itself. This study aims to see the influence of internal factors of the taxpayer's self, namely the awareness of taxpayers and income owned as well as external external factors, socialization and quality of service to compliance with UN P2 pay in Pontianak City.Data retrieval techniques are carried out by spreading questionnaires with non-probability sampling techniques purposive sampling methods with research sample criteria and obtained samples of as many as 100 people. Data analysis techniques are validity tests, reliability tests, descriptive statistical analysis, classical assumption tests, multiple linear regression analysis and hypothesis tests using the SPSS version 25 program. The conclusion obtained is the awareness of the taxpayer, compulsory income and socialization. has a positive effect on taxpayer compliance in paying PBB-P2 in Pontianak City while service quality has no effect on taxpayer compliance in paying PBB-P2 in Pontianak City.